Effective Migration Policy as Factor of Ensuring Economic Security of the Regions - DANILOV, Ivan P.; ILYINA, Ekaterina A.; LADYKOVA, Tatiana I.; MOROZOVA, Natalia V. (Journal of Advanced Research in Law and Economics, 2017)
Relevance of the studied problem is caused by the fact that at the regional level the principles of migration policy are still not developed, not all factors of influence of migratory processes on economic security of regions are defined; characteristics and consequences of labor migration are insufficiently investigated. In this regard, this article is directed to the solution of the problem of population shift, demanding development and realization of the regional migration policy aimed at providing and preservation of safety of host. The leading approach to a research of this problem is economical and statistical, allowing establishing dependence between the predicted size of labor migration and factors influencing it. The designed model of sustainable development of the region has to include the regional migration policy considering factors of forecasting of migratory processes that will allow to stabilize and increase the number of resident population and to provide innovative development of the region and country in general. Materials of the article can be useful when developing approaches promoting formation of the scientifically based and effective regional migration policy providing the balanced dynamic social and economic development of the region.